Development of a 2-Nitrobenzoate-Sensing Bioreporter Based on an Inducible Gene Cluster - Deb, Satamita; Basu, Soumik; Singha, Achintya; Dutta, Tapan K. (Frontiers in Microbiology, 2018)
Based on the sole information of structural genes of the 2-nitrobenzoate (2NBA) utilizing catabolic gene cluster (onbX1X2FCAR1EHJIGDBX3), 2NBA-sensing bioreporters were constructed by incorporating egfp into the onb gene cluster of Cupriavidus sp. strain ST-14. Incorporation of reporter gene in proximal to the hypothesized promoter region in conjunction with the disruption of the gene encoding inducer-metabolizing enzyme was turned out to be advantageous in reporter gene expression at low inducer concentration. The bioreporter strain was capable of expressing EGFP from the very first hour of induction and could detect 2NBA at (sub)nanomolar level exhibiting a strict specificity towards 2NBA, displaying no response to EGFP expression from its meta- and para-isomers as well as from a number of structurally related compounds. The present study is a successful demonstration of the development of a 2NBA-sensing bioreporter with respect to ease of construction, inducer specificity and sensitivity, without prior knowledge of the associated inducer-responsive promoter-regulator elements. The present approach can be used as a model for the development of bioreporters for other environmental pollutants.